Transformational leadership and motivation’s influence on teacher innovation and job satisfaction - Utami, Batina Yulia; Susanti, Lusi; Rusdinal , Rusdinal; Achyar , Novriyanti (Universitas Jambi, Indonesia, 2026)
This research investigated the influence of principals' transformational leadership and achievement motivation on teachers' innovative behavior, mediated by teacher job satisfaction, in public junior high schools in Pesisir Selatan Regency. This research used a quantitative, causal-associative approach to examine the direct and indirect effects of principals' transformational leadership and achievement motivation on innovative behavior via teacher job satisfaction. This research involved 384 civil servant teachers from a population of 2,118. Data were collected using a questionnaire and analyzed using PLS-SEM (Partial Least Squares Structural Equation Modeling). The results indicated that transformational leadership had a positive and significant effect on teachers' innovative behavior, with a coefficient of 0.407 (p < 0.05). However, achievement motivation had a negative but significant effect on innovative behavior (coefficient: -0.174, p < 0.05). Teacher job satisfaction was found to have a strong positive effect on innovative behavior (coefficient: 0.707, p < 0.05).